Hoop Houses Provide Optimal Conditions for Increased Crop Production Year-round - Newberry, Sue (Proceedings of the West Virginia Academy of Science, 2023)
I worked with the non-profit organization Eco Vrindavan Inc., located in Moundsville West Virginia to grow and provide organic food to the local community. Wheeling’s Grow Ohio Valley, an organization that supports local food production, assisted in installing “hoop houses” which increase the length of the growing season and increase production. Hoop houses are unheated structures covered in plastic where crops are planted directly into the ground. While working for Eco Vrindavan Inc., I observed how hoop houses extend the growing season by keeping the ground from freezing and ensuring the survival of selected crops through winter months. During this internship, I grew, planted, and harvested various greens in order to provide produce to the community. I learned what types of greens do well in cold climates and which ones do not and I have gained experience in how to organically fertilize plants, check soil quality, and look for mites and other diseases on crops. Currently, preparation for spring planting is underway to ensure early crops of flowers and summer vegetables. Hoop houses may provide benefits to organic growers who need crops to be available all year long and help minimize labor costs by keeping pests away while ensuring temperature changes do not negatively affect crops. In the future, I hope to educate other organic growers on the benefits hoop houses provide and use what I have learned to introduce organic growing in hoop houses to more communities statewide.